5 UMPSA senior lecturers promoted to Professor Grade VK7 - Siti Sakinah, Mohtar (UMPSA, 2025)
GAMBANG, 19 June 2025 – Five senior lecturers from Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) have been officially promoted to the position of Professor, Special Grade C (VK7), during a session held at the Vice-Chancellor’s Office, Chancellery Building, UMPSA Gambang Campus.